2014
DOI: 10.1002/mrc.4164
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aging and solvent treatments of painted surfaces using single‐sided NMR

Abstract: Typical experiments conducted with single-sided NMR are incapable of unique chemical identification and, thus, often rely on comparative measurements in scientific study. However, cultural heritage objects have unique natures and histories, making a genuine 'control' sample a rarity and complicating many scientific investigations. In this paper, we present some comparative results enabled by such a rare, control sample. Two paintings, The Dinner and The Dance from the 1616 set Pipenpoyse Wedding, were made by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
(28 reference statements)
1
36
0
4
Order By: Relevance
“…The NMR‐MOUSE proved to be a useful tool for the comparative analysis of materials and techniques used in paintings. Thus, when studying two paintings, The Dinner and The Dance , from the Pipenpoyse Wedding series made by the same artist with the same materials and methods, Fife et al observed differences in the transverse relaxation times between the painted treated by a conservator ( The Dinner ) and the untreated painting ( The Dance ) . This exemplifies the feasibility of this method to be applied for comparative analysis of paintings, opening the possibility of using this method to examine differences between authentic and forged paintings, where a comparative analysis could reveal differences in the techniques and materials used by the painter and by the forger.…”
Section: Mobile Nmr Applicationsmentioning
confidence: 97%
“…The NMR‐MOUSE proved to be a useful tool for the comparative analysis of materials and techniques used in paintings. Thus, when studying two paintings, The Dinner and The Dance , from the Pipenpoyse Wedding series made by the same artist with the same materials and methods, Fife et al observed differences in the transverse relaxation times between the painted treated by a conservator ( The Dinner ) and the untreated painting ( The Dance ) . This exemplifies the feasibility of this method to be applied for comparative analysis of paintings, opening the possibility of using this method to examine differences between authentic and forged paintings, where a comparative analysis could reveal differences in the techniques and materials used by the painter and by the forger.…”
Section: Mobile Nmr Applicationsmentioning
confidence: 97%
“…[60] This effect was reliably observed in two paintings from 1616 by the same artist, one in its original state,the other one having been cleaned with solvents at least twice (Figure 6). [35] Theo pposite effect is observed when repairing an object with an elastic consolidant, or when employing stone strengthener to repair weathered stone. [24,62] Moreover,h ydrophobic substances are employed to reduce capillary water uptake while keeping the pore network intact so that the stone can still transport water vapor.…”
Section: Conservation Treatmentsmentioning
confidence: 99%
“…B, Accelerated light aging (top) and natural aging over hundreds of years of tempera paint . C, “The Dinner” and “The Dance” painted in 1616 (top) and T 2 depth profiles through the paint layers suggesting differences between natural aging and aging by solvent cleaning…”
Section: Aging Of Polymersmentioning
confidence: 99%
“…The NMR‐MOUSE, in fact, is a highly suitable tool to follow the solvent ingress and drying in paint and polymer layers (S Prati, G Sciutto, F Volpi, C Rehorn, R Vurro, B Blümich, L Mazzocchetti, L Giorgini, C Samorì, P Galletti, E Tagliavini, R Mazzeo, under review). With each solvent exposure, not only varnish is removed, but low molecular weight compounds are also washed out from the paint layer as suggested by a comparative study of two paintings from 1616, one in its original state and the other having been restored by solvent cleaning (Figure C) . While the paint layer in its original state shows a T 2 gradient across its width with low values near the surface and higher ones deeper down, the paint layer from the restored painting shows the low T 2 value across its entire width.…”
Section: Comparison With Aging Of Paintmentioning
confidence: 99%
See 1 more Smart Citation